2020
DOI: 10.3233/xst-200662
|View full text |Cite
|
Sign up to set email alerts
|

Developing and verifying automatic detection of active pulmonary tuberculosis from multi-slice spiral CT images based on deep learning

Abstract: OBJECTIVE: Diagnosis of tuberculosis (TB) in multi-slice spiral computed tomography (CT) images is a difficult task in many TB prevalent locations in which experienced radiologists are lacking. To address this difficulty, we develop an automated detection system based on artificial intelligence (AI) in this study to simplify the diagnostic process of active tuberculosis (ATB) and improve the diagnostic accuracy using CT images. DATA: A CT image dataset of 846 patients is retrospectively collected from a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…CTVE is a computer software function that processes the images obtained from spiral CT volume scanning to simulate a threedimensional image of the inner surface of the cavity, which can simulate the view of an endoscope to observe the interior of the cavity. It has the advantages of short time, noninvasive, and good tolerance, and it can also use the data for multiple, multiplanar reconstruction to reduce the leakage caused by human factors [17]. Although it started late, as an emerging technique for endoluminal imaging, it is particularly useful for some patients who are unable or unwilling to do invasive endoscopy [18].…”
Section: Introductionmentioning
confidence: 99%
“…CTVE is a computer software function that processes the images obtained from spiral CT volume scanning to simulate a threedimensional image of the inner surface of the cavity, which can simulate the view of an endoscope to observe the interior of the cavity. It has the advantages of short time, noninvasive, and good tolerance, and it can also use the data for multiple, multiplanar reconstruction to reduce the leakage caused by human factors [17]. Although it started late, as an emerging technique for endoluminal imaging, it is particularly useful for some patients who are unable or unwilling to do invasive endoscopy [18].…”
Section: Introductionmentioning
confidence: 99%
“…This design idea has many technical advantages that single-source CT is not prepared for, and it is a milestone breakthrough in the history of CT development [ 5 ]. Ma et al proposed diagnosing the artificial neural network-assisted CT image in medicine [ 6 ]. Mohandes et al showed that CT has high sensitivity and specificity in the imaging diagnosis of the trachea and bronchial foreign bodies, with an accuracy of up to 97%, providing outstanding contributions to the diagnosis and differential diagnosis of difficult cases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It relies on the further understanding of the anatomy of the aortic sinus and its frequent adjacent tissues. At present, there are a few studies in China and abroad, and most of them focus on animal observation, autopsy, or visual observation during cardiac surgery, which lacks clinical guidance [ 8 ]. This is achieved by the slip ring technology and a continuous flat movement of the scanning bed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%